Development of myocarditis and pericarditis after COVID‐19 vaccination in children and adolescents: A systematic review. Issue 3 (2nd January 2023) - Fatima, Maurish; Khan, Muhammad H. A.; Ali, Muhammad S.; Osama, Muhammad; Cheema, Huzaifa A.; Ahmed, Aleena; Nisar, Amna; Murad, Muhammad W.; Farooq, Hareem; Rehman, Muhammad A. U.; Swed, Sarya; Akbar, Usman A.
Abstract: Myocarditis and pericarditis have been reported after COVID‐19 vaccine administration in children and adolescents, raising the concern about their possible association with these vaccines. The objective was to explore the incidence, clinical presentation, and association of myocarditis and pericarditis with COVID‐19 vaccines in children and adolescents. We conducted a systematic literature search on three databases, that is, Cochrane, MEDLINE/PubMed, and EMBASE from inception till March 2022. A total of three case reports, four case series, and six observational studies were included in the review. For case reports and case series, the mean age of the patients was 17.4 years, with 96.9% being male. Chest pain ( n = 31, 93.9%), fever ( n = 18, 54.5%), myalgias ( n = 15, 45.4%) and headache ( n = 9, 27.2%) were the most common presentations. Out of 33 patients, 32 (96.9%) of patients received Pfizer‐BioNTech whereas only one (3.03%) received Moderna (mRNA 1273). Clinical investigations revealed ST elevation ( n = 32, 97%), and elevated CRP ( n = 9, 27.2%) and cardiac troponin ( n = 29, 87.8%). The pooled incidence of myocarditis and pericarditis from observational studies was (0.00063%) and (0.000074%) %, respectively. Myocarditis and pericarditis in children and adolescents after the COVID‐19 vaccines were more prevalent among males and more commonly observed after the second dose of Pfizer. Though the overall incidence was low, however, the clinicians should consider myocarditis and pericarditis as probable diagnosis when encountering young patients, with a history of vaccine administration, presenting with suggestive findings.